Minimum 2-year outcomes and return to sports of competitive athletes who undergo subspine decompression during primary hip arthroscopy for femoroacetabular impingement syndrome and subspine impingement: A propensity-matched controlled study - Jimenez, A. E.; Lee, M. S.; George, T.; Owens, J. S.; Harris, W. T.; Maldonado, D. R.; Lall, A. C.; Domb, B. G. (The American Journal of Sports Medicine, 2022)
Background: Patient-reported outcomes (PROs) and return to sports (RTS) have not been established in athletes undergoing primary hip arthroscopy and subspine decompression for femoroacetabular impingement syndrome (FAIS) and subspine impingement (SSI).